Teacher-level and context-level barriers to using English as a medium of instruction: A systematic review - Loy, Chee Luen; Abdul Wahab, Norwaliza (Journal of research, policy & practice of teachers & teacher education, 2020)
A systematic review of literature regarding the factors that hinders or challenges preschool teachers’ use of the English language in formal preschool classrooms was undertaken initially in order to summarize the findings of research between 1991 and 2016. Research suggested that various important teacher and context level barriers were barriers. Large number of literature reported preschools teachers’ lack of confidence in using the language as the prevalent barrier, followed by lower than expected proficiency level. The literature alluded to an association between these two teacher barriers. Other teacher context included inability to differentiate instruction to meet the needs of all learners when English was solely used, deficient attitudes and beliefs about the importance of the language thus creating an inherent resistance to use the language in the classroom, and stress related workplace due to overzealous administrators. Context level barriers included time constraints, classroom environment (example, lack of access to resources, large classroom sizes, and lack of parental encouragement towards the use of English), and lack of administrative support.